Pola Asuh Orang Tua dalam Membentuk Kecerdasan Emosional Peserta Didik di SD Negeri 1 Tatura Palu: Pola Asuh orang tua - mita, Nirmalasasmitasari (Khirani: Jurnal Pendidikan Anak Usia Dini, 2026)
This research focuses on understanding how different parenting styles influence the emotional intelligence of students, along with the factors that either facilitate or obstruct these parenting approaches in developing emotional intelligence at SD Negeri 1 Tatura Palu. The motivation behind this study stems from the significance of emotional intelligence in young elementary students, which is linked to their capability to recognize, manage, and positively express their emotions in everyday situations. Variations in students’ emotional skills are shaped by the parenting styles utilized by parents in their household. A qualitative method is employed in this study, using a descriptive research framework. Data was gathered through methods such as observations, interviews, and documents, involving participants that included educators, parents, and fifth-grade pupils. The analysis of data involved reducing, presenting, and verifying it, while the validity of the data was assessed through source triangulation. Findings from the study reveal that parenting styles among parents include democratic, permissive, and partially authoritarian approaches. The democratic style emerged as the most prevalent and positively impacted the enhancement of students’ emotional intelligence, including skills like managing emotions, self-assurance, empathy, and social abilities. Factors that support the development of emotional intelligence were found to be parental care and affection, open lines of communication, and providing encouragement.